1994
DOI: 10.1161/01.atv.14.7.1146
|View full text |Cite
|
Sign up to set email alerts
|

HDL and plasma phospholipids in coronary artery disease.

Abstract: Lipid fractions of native plasma and of highdensity lipoprotein (HDL) were analyzed, and the clotting times of native platelet-rich and -poor plasma were recorded in patients with coronary artery disease and age-matched control subjects not taking any medication known to alter plasma lipid levels, coagulation, or platelet aggregation. Patients with coronary artery disease had lower HDL cholesterol and particularly HDL phospholipids but elevated HDL triglycerides, plasma triglycerides and diglycerides, and fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 0 publications
3
26
0
1
Order By: Relevance
“…Several studies have demonstrated a positive correlation between the PL/C of HDL and the capacity of serum to accept cellular cholesterol (40)(41)(42). Furthermore, it has been suggested that a low PL/C in HDL is associated with an increased risk for ischemic vascular disease (43) and coronary artery disease (44). Our data, therefore, suggest that the HDL particles secreted in the presence of 18L and 37pA might be more efficient in promoting cholesterol efflux from the cells.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Several studies have demonstrated a positive correlation between the PL/C of HDL and the capacity of serum to accept cellular cholesterol (40)(41)(42). Furthermore, it has been suggested that a low PL/C in HDL is associated with an increased risk for ischemic vascular disease (43) and coronary artery disease (44). Our data, therefore, suggest that the HDL particles secreted in the presence of 18L and 37pA might be more efficient in promoting cholesterol efflux from the cells.…”
Section: Discussionmentioning
confidence: 53%
“…The higher apoA-I/ apoB and PL/C ratios, considered good indicators of negative risk for coronary artery disease (40)(41)(42)(43)(44), and the for- Fig. 4.…”
Section: Discussionmentioning
confidence: 99%
“…PON1 activity is substantially lower in patients with CAD, ACS, CKD, and RA, whereas lipoprotein-associated phospholipase A 2 (LpPLA 2 ) activity is increased in CKD and psoriasis (89,137,160,165,(171)(172)(173)(174)(175). Dysregulating the activity of PON1 and LpPLA 2 in this fashion not only compromises the antioxidative activity of HDL, but also promotes the formation of atherosclerotic plaques.…”
Section: Composition and Role Of Hdl-associated Proteinsmentioning
confidence: 99%
“…The efflux of cholesterol from cells to serum is correlated with HDL PL content (17,18). Importantly, it has been demonstrated that patients with coronary artery disease have low HDL PL levels (19). Past studies have used in vitro manipulation of HDL composition to probe the relationships between HDL PL and cell cholesterol flux.…”
mentioning
confidence: 99%